2019
DOI: 10.1101/2019.12.16.876888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disassembly of Tau fibrils by the human Hsp70 disaggregation machinery generates small seeding-competent species

Abstract: The accumulation of amyloid Tau aggregates is implicated in Alzheimer’s disease and other Tauopathies. Molecular chaperones are known for their function in maintaining protein homeostasis by preventing the formation or promoting the disaggregation of amorphous and amyloid protein aggregates. Here we show that an ATP-dependent human chaperone system disassembles Tau fibrils in vitro. This function is mediated by the core chaperone Hsc70, assisted by specific co-chaperones, in particular class B J-domain protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
1
23
0
3
Order By: Relevance
“…Overall, we discovered 9 Hsp40s that co-purified with tau across each tau IP (Supplementary Data 1). Amongst them, we identified Hsp40s, including DnaJA2, DnaJB1 and DnaJB6, which have been previously implicated in binding amyloidogenic substrates to control fibril assembly or disassembly [30][31][32]. We find that tau signal intensity increased 10-fold across this time window and most chaperones trend with tau signal with some notable exceptions, signal intensity for DnaJC7 decreased 5-fold while for DnaJC5 it increased nearly 50-fold (Supplementary Fig.…”
Section: Dnajc7 Influences Tau Seeding In Vivo and In Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…Overall, we discovered 9 Hsp40s that co-purified with tau across each tau IP (Supplementary Data 1). Amongst them, we identified Hsp40s, including DnaJA2, DnaJB1 and DnaJB6, which have been previously implicated in binding amyloidogenic substrates to control fibril assembly or disassembly [30][31][32]. We find that tau signal intensity increased 10-fold across this time window and most chaperones trend with tau signal with some notable exceptions, signal intensity for DnaJC7 decreased 5-fold while for DnaJC5 it increased nearly 50-fold (Supplementary Fig.…”
Section: Dnajc7 Influences Tau Seeding In Vivo and In Cellsmentioning
confidence: 79%
“…To understand the abundance of the different Hsp40s bound as a function of tau changes we normalized the Hsp40 signal intensity according to the 1N4R tau intensities (see methods). Recently, Hsp40s have been implicated in directly modulating protein aggregation [30][31][32]. We wanted to determine how the levels of these associated Hsp40s changed as a function of tau seeding activity.…”
Section: Dnajc7 Influences Tau Seeding In Vivo and In Cellsmentioning
confidence: 99%
“…This indicates a possible ensemble of aggregation-prone monomeric conformers that have the capacity to adopt and propagate distinct fibrillar conformations [15]. The idea that tau monomer alone can drive its assembly and serve as a template to form structural polymorphs is not widely accepted, although recent work from other groups on tau [16], and Sup35 [17], are consistent with this idea.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, mounting evidence has indicated that Hsp70 chaperones are also involved in the disassembly of aggregates and capable of disaggregating even persistent amyloidogenic aggregate structures such as αS, HTT and Tau fibrils 1726 . In particular, the constitutively expressed chaperone heat shock complement Hsc70 (HSPA8) together with the Hsp40 class B J-protein DnaJB1 and the Hsp110 family nucleotide exchange factors (NEFs) Apg2 or Hsp105α have been demonstrated to constitute a powerful ATP-driven disaggregase system that disassembles amyloids within minutes via combined fibril fragmentation into shorter fibrils, promoting their depolymerisation into monomers or smaller oligomeric structures 1719 .…”
Section: Introductionmentioning
confidence: 99%